(untitled) (European Journal of Interdisciplinary Research and Development, 2025)
This article studied patients with IDA, determined the mild degree of the disease in children and highlighted the general condition of the examined patients. It is explained that it causes anemia, gastrointestinal tract problems, rickets, and frequent colds.